Inside Cover: Determination of a metabolite of nifursol in foodstuffs of animal origin by liquid–liquid extraction and liquid chromatography with tandem mass spectrometry. Issue 3 (February 2017) - Wang, Chuanxian; Qu, Li; Liu, Xia; Zhao, Chaomin; Zhao, Fengjuan; Huang, Fuzhen; Zhu, Zhenou; Han, Chao
Abstract : J. Sep. Sci . 2017, 40, 671–676 DOI:10.1002/jssc.201600996 The cover picture shows a schematic map of an analytical method developed for the detection of a metabolite of nifursol, 3, 5‐dinitrosalicylic acid hydrazide (DNSAH), in foodstuffs of animal origin (chicken liver, pork liver, lobster, shrimp, eel, sausage and honey). Samples were hydrolyzed with hydrochloric acid and derivatized with 2‐nitrobenzaldehyde at 37 °C for 16 h. The solutions of derivatives were adjusted to pH 7.0–7.5, and the metabolite was extracted with ethyl acetate. The solutions was centrifuged and used in LC‐MS/MS determination.